Sabilulungan Class Programe in School as an Effort to Integrate Value of Local Wisdom in Education in Bandung, West Java Indonesia - Peny Husna Handayani (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
Bandung society is synonymous with Sundanese culture, accepting the impact of the flow of modernization that causes the forgotten values of local cultural wisdom. Local wisdom should be sustained for characters building of the next generation . It is time for local wisdom to be rewarded, reorganized, and re-taught in the education system through educational and learning activities at school. Reintroducing the values of local cultural wisdom to the next generation is considered to be a very important thing to save the morality of the next generation also saves the culture itself. The value of local wisdom sabilulungan imbued by the philosophy of Sundanese silih asah, silih asih, silih asuh, became the core of Sundanese culture that needs to be integrated in the process of education in school. In this paper will describe a way or program that allows the value of local wisdom Sundanese culture, sabilulungan, integrated in the education system, especially for people in the city of Bandung.